2022
DOI: 10.1038/s41380-022-01513-x
|View full text |Cite
|
Sign up to set email alerts
|

Cav3.1-driven bursting firing in ventromedial hypothalamic neurons exerts dual control of anxiety-like behavior and energy expenditure

Abstract: The central nervous system has evolved to coordinate the regulation of both the behavior response to the external environment and homeostasis of energy expenditure. Recent studies have indicated the dorsomedial ventromedial hypothalamus (dmVMH) as an important hub that regulates both innate behavior and energy homeostasis for coping stress. However, how dmVMH neurons control neuronal firing pattern to regulate chronic stress-induced anxiety and energy expenditure remains poorly understood. Here, we found enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Acute or chronic stress is associated with a higher risk of many psychological disorders, including anxiety and depressive disorders 41 , 42 . As the CeA is the main information output nucleus in the amygdala, many studies have reported that CeA hyperactivity following exposure to stress or stressor events contributes to the pathogenesis of anxiety 23 , 43 , 44 ; these findings are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Acute or chronic stress is associated with a higher risk of many psychological disorders, including anxiety and depressive disorders 41 , 42 . As the CeA is the main information output nucleus in the amygdala, many studies have reported that CeA hyperactivity following exposure to stress or stressor events contributes to the pathogenesis of anxiety 23 , 43 , 44 ; these findings are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…4), could increase ethanol resistance in WT mice. Reducing MD firing using phasic inhibition under ethanol, potentially leading to inhibition and rebound burst 52 , could also increase the duration of the fLOM in WT mice injected with a lower dose of ethanol (Figure S12; 2.0 g/kg). We propose that the relative change in firing rate in MD RS neurons might be an important driver and indicator of the change of transition in and out of consciousness as demonstrated for other nuclei of the dMT 8,9,32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…The VMH serves as a critical hub for transmitting and processing stress-related information inputs, thereby playing a regulatory role in the homeostasis of peripheral tissues, such as bone (Yang et al, 2020) and adipose (Viskaitis et al, 2017;Shao et al, 2022). However, the synaptic mechanism responsible for VMH activation following chronic stress remains unclear.…”
Section: Excitatory Synaptic Inputs Into the Vmh Increase After Chron...mentioning
confidence: 99%
“…The VMH also serves as a vital hub linking emotional states and peripheral physiological homeostasis (Fioramonti et al, 2009;Kuperman et al, 2010;Anderson, 2016;Viskaitis et al, 2017). Recent studies from our research group revealed profound electrophysiological and molecular changes within the VMH following chronic stress, precipitating anxietylike emotional states and disruptions in peripheral metabolic equilibrium (Yang et al, 2020;Shao et al, 2022). For example, chronic stress over a 4-week period has been shown to enhance projections from the bed nucleus of the stria terminalis (BNST) to the VMH, thereby provoking anxiety-like behavior and specifically affecting bone loss (Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation